Optical verification and in-vitro characterization of two commercially available acoustic bubble counters for cardiopulmonary bypass systems. (January 2018) - Segers, Tim; Stehouwer, Marco C.; de Somer, Filip M.J.J.; de Mol, Bastian A.; Versluis, Michel
Introduction: Gaseous microemboli (GME) introduced during cardiac surgery are considered as a potential source of morbidity, which has driven the development of the first bubble counters. Two new generation bubble counters, introduced in the early 2000s, claim correct sizing and counting of GME. This in-vitro study aims to validate the accuracy of two bubble counters using monodisperse bubbles in a highly controlled setting at low GME concentrations. Methods: Monodisperse GME with a radius of 43 µm were produced in a microfluidic chip. Directly after their formation, they were injected one-by-one into the BCC200 and the EDAC sensors. GME size and count, measured with the bubble counters, were optically verified using high-speed imaging. Results: During best-case scenarios or low GME concentrations of GME with a size of 43 µm in radius in an in-vitro setup, the BCC200 overestimates GME size by a factor of 2 to 3 while the EDAC underestimates the average GME size by at least a factor of two. The BCC200 overestimates the GME concentration by approximately 20% while the EDAC overestimates the concentration by nearly one order of magnitude. Nevertheless, the calculated total GME volume is only over-predicted by a factor 2 since the EDAC underestimates the actual GME size. For the BCC200, the total GME volume was over-predicted by 25 times due to the over-estimation of GME size. Conclusions: The measured errors in the absolute sizing/counting of GME do not imply that all results obtained using the bubble counters are insignificant or invalid. A relative change in bubble size or bubble concentration can accurately be measured. However, care must be taken in the interpretation of the results and their absolute values. Moreover, the devices cannot be used interchangeably when reporting GME activity. Nevertheless, both devices can be used to study the relative air removal characteristics of CPB components or for the quantitative monitoring of GME production during CPB interventions.